2022
DOI: 10.3390/plants11131738
|View full text |Cite
|
Sign up to set email alerts
|

The Content of Certain Groups of Phenolic Compounds and the Biological Activity of Extracts of Various Halophyte Parts of Spergularia marina (L.) Griseb. and Glaux maritima L. at Different Levels of Soil Salinization

Abstract: Halophyte plants are known for their resistance to harsh environmental conditions associated with excess salts in their habitats. Their resistance to salinization is due, among other things, to their high ability to detoxify free radicals, owing to the relatively high content of antioxidants. On the coast of the Baltic Sea and in the lagoons, there are several rare halophyte species included in the Red Book of the Kaliningrad Region (Russia) and the Baltic region, such as Spergularia marina (L.) Griseb. and Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…However, a study on halophyte plants reported a decrease in the apigenin derivative level as salinity increased in Spergularia marina (L.) Griseb. (Pungin et al ., 2023), which is consistent with our findings. After 24 h, unencapsulated AP retained 69.05%, 60.31% and 52.25% of the AP content at NaCl levels of 0.1 M, 0.3 M and 0.5 M respectively.…”
Section: Resultssupporting
confidence: 94%
“…However, a study on halophyte plants reported a decrease in the apigenin derivative level as salinity increased in Spergularia marina (L.) Griseb. (Pungin et al ., 2023), which is consistent with our findings. After 24 h, unencapsulated AP retained 69.05%, 60.31% and 52.25% of the AP content at NaCl levels of 0.1 M, 0.3 M and 0.5 M respectively.…”
Section: Resultssupporting
confidence: 94%
“…In the halophytes studied herein, 46 of the 94 tentatively identified compounds were hydroxycinnamic acids [ 75 ], mostly derivatives of caffeic acid ( Figure A1 A), ferulic acid ( Figure A1 B), p -coumaric acid ( Figure A1 C), and sinapic acid ( Figure A1 D), showing the typical molecular ion [M−H] − at m / z 179 (compounds 5 , 8 , 11 , 15 , 20 , 21 , 30 , 32 , 61 , 67 , 74 , 80 , 81 , 84 , and 86 ), m / z 193 (compounds 18 , 19 , 22 , 24 , 29 , 40 , 43 , 89 , 90 , and 94 ), m / z 163 (compounds 1 , 12 , 13 , 23 , 34 , 38 , 39 , 41 , 44 , 47 , 54 , 56 , 62 , 66 , 71 , 75 , 77 , 78 , 88 , and 93 ), and m / z 223 (compound 26 ) in the corresponding mass fragmentation spectra, Table A1 — Appendix A . The presence of these hydroxycinnamic acid derivatives was previously reported in S. ramosisssima [ 76 ], in conventional and microwave S. ramosissima extracts [ 77 ], as well as in other halophyte plants such as Glaux maritima roots [ 78 ], and in C. maritimum [ 79 ], as a survival molecular adaptation to saline soil conditions, as described by Pungin et al [ 78 ].…”
Section: Resultsmentioning
confidence: 75%
“…The lower content of D. crassifolium and M. crystallinum species in salt showed a positive association with the absence of hydroxybenzoic acids in these plants. As described by Pungin et al [ 78 ] and Qasim et al [ 85 ], despite the plant’s adaptive variability in salt environmental conditions, the phenolic compounds, particularly the phenolic acids, accumulate in the halophytes as a protective response against the oxidate stress imposed by the soil salinization; therefore, in the plants with lower salt content a lower phenolic content is expected. From a quantitative point of view, S.ramosissima showed the highest content of hydroxybenzoic acids, which is particularly thanks to the protocatechuic acid arabinoside (compound 9 ) content, Table 6 and Table S1—Supplementary Materials .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological active compounds, such as polyunsaturated fatty acids, vitamins, sterols, essential oils, polysaccharides, glycosides, and phenolic compounds, have recently been described in extracts of S. marina (Pungin et al. 2022 ).…”
Section: Introductionmentioning
confidence: 99%